Salience Matters: Filler groups on the ascent of human scale impact ratings for target groups. - Devin L Johnson; Sukhvinder S Obhi (PLoS ONE, 2023)
Researchers using the ascent of human scale (AOH) to study dehumanization typically include filler groups in addition to the main comparator groups, to hide the true intent of the study. However, there is little work examining the impact of filler group choice on dehumanization ratings between groups of interest. Across two studies (including one pre-registered study) we manipulated the salience of a target out-group (i.e., the extent to which the group stood out) by embedding it within lists of other groups. By comparing AOH ratings across three conditions in which the target out-group was either high salience, medium salience, or low salience, we were able to determine the effects of target out-group salience on dehumanization. In study 1, we included participants' in-group (Canadian) in the list, and in study 2, we did not include participants in-group in the list. Results from study 1 showed that group salience had no impact on AOH ratings for the out-group when the participant in-group was included in the list. However, in study 2, when participant in-group was removed from the list, ratings for the out-group in the high salience condition were significantly lower than both the medium and low salience conditions. Implications for both theoretical and methodological issues in investigations using the AOH scale are discussed.